Proceedings of the 22nd ACM/IEEE Joint Conference on Digital Libraries 2022
DOI: 10.1145/3529372.3533287
|View full text |Cite
|
Sign up to set email alerts
|

Asking for help in community question-answering

Abstract: Communityquestion-answering (CQA) enables both information retrieval and social interactions. CQA questions are viewed as goal-expressions from the askers' perspectives. Most prior studies mainly focused on the goals expressed in the questions, but not on how responders' expectations and responses are influenced by the goal-expressions. To fill the gap, this research proposes the use of framing theory to understand how different expressions of goals influence responses. Cues of questions were used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…First, goal‐frames attract attention to different goals (Lindenberg, 2018). Past studies revealed that question cues such as specialized details and complexity attract attention to cognitive demands for problem‐solving (Te'eni, 1990; Wu et al, 2022). Hence, question cues might construct goal‐frames for responders.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…First, goal‐frames attract attention to different goals (Lindenberg, 2018). Past studies revealed that question cues such as specialized details and complexity attract attention to cognitive demands for problem‐solving (Te'eni, 1990; Wu et al, 2022). Hence, question cues might construct goal‐frames for responders.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…First, complexity refers to the difficulty to solve a problem (Byström & Järvelin, 1995). For responders, it indicates the cognitive effort required for problem‐solving (Te'eni, 1990; Wu et al, 2022). Second, specificity examines the richness of details to clarify the problem (Banerjee, 2017).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations